UJI FITOKIMIA DAN ANTIBAKTERI EKSTRAK METANOL DAUN MAHONI (Swietenia mahagoni (L.) Jacq) - Sandra, Putri Ayu; Daniel, Daniel; Saleh, Chairul (Jurusan Kimia FMIPA UNMUL, 2021)
Antibacterial activity test of methanol extract of Mahoni (Swietenia mahagoni (L) jacq) leaves was carried out. Extraction Mahogany leaf samples was carried out by maceretion method using methanol as a solvent. Antibacterial activity test was carried out using agar diffusion method, by spreading bacteria to agar media, then the extract was placed using disc paper. Phytochemical test result showed that the methanol extract of Mahoni leaf contained secondary metabolites of flavonoid, triterpenoid, steroid, saponin dan phenolic compounds. The antibacterial activity test result obtained Minimum Inhibitory Concentration (MIC) values for Streptococcus mutans bacteria were 0-0,625% and for Salmonella typhi bacteria 0-0,625%.